Unveiling fungal infections and immune responses in redclaw crayfish - Shekinah Shamini Victor (2024)
Redclaw crayfish, Cherax quadricarinatus, is also referred to as freshwater lobster in Malaysia and is consumed widely since it is commercially produced by entrepreneurs and readily available in restaurant chains. This species is imported from Australia and Indonesia and is a profitable industry. Aphanomyces astaci was identified as the cause of crayfish plague in parts of Asia and Europe. Understanding the biological threats such as A. astaci and otherinfections are critical towards the survival of the industry. In this study, the fungal strains responsible for causing infections similar to crayfish plague were isolated, and the genetic connection between the identified fungal strains and A. astaci were investigated. The fungi were isolated from crayfish exhibiting infection symptoms, such as melanisation, abdominal whitening, and sluggish movement. Genomic DNA from the fungi was extracted, amplified, sequenced, and analyzed using primers ITS86F and ITS4. The sequences were aligned with reference sequences from GenBank, and a neighbor-joining tree was constructed to determine sequence similarity and phylogenetic relationships. Fourteen morphologically different fungi were identified, primarily filamentous, whitish, and cottony, closely related to wood-decaying fungi. These fungi may be linked to A. astaci, the causative agent of crayfish plague. The study also investigated the expression of immune genes (ferritin 3 and laminin receptor) in infected crayfish, revealing their significant roles in the immune system. Ferritin is a biomarker for inflammatory diseases and an iron storage component, while laminin receptor protects organisms from infection. The findings of this study will assist towards developing treatment and prevention of fungi that cause crayfish plague and development of vaccines that are able to cure crayfish plague.